2013
DOI: 10.1094/ats-2013-0328-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preemergence Herbicides on the Recovery of Bermudagrass from Spring Dead Spot

Abstract: Field experiments were conducted in Texas to examine the recovery of a bermudagrass [Cynodon dactylon × C. transvaalensis (L.) Pers.] fairway from spring dead spot (SDS) disease following preemergence (PRE) herbicide applications. In 2011 and 2012 bermudagrass recovery from SDS in the non‐treated check plots (46 and 59%, respectively) was similar to bermudagrass recovery in response to oxadiazon at 3.4 kg/ha (55 and 57%, respectively) 14 weeks after treatment (WAT). Pendimethalin at 2.5 kg/ha resulted in 33 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…ha −1 reduced root mass and reduced magnesium and manganese content in hybrid bermudagrass foliage compared with the nontreated check; however, investigators evaluated higher indaziflam rates in systems that contained less organic matter compared with the presented research. These data agree with previous research indicating that oxadiazon does not adversely affect hybrid bermudagrass rooting (Fishel and Coats, 1993; Beck et al, 2013).…”
Section: Resultssupporting
confidence: 93%
“…ha −1 reduced root mass and reduced magnesium and manganese content in hybrid bermudagrass foliage compared with the nontreated check; however, investigators evaluated higher indaziflam rates in systems that contained less organic matter compared with the presented research. These data agree with previous research indicating that oxadiazon does not adversely affect hybrid bermudagrass rooting (Fishel and Coats, 1993; Beck et al, 2013).…”
Section: Resultssupporting
confidence: 93%
“…It is well established that root-inhibiting herbicides can reduce the speed at which turfgrasses can spread or recover from injury or disease. Beck et al (2013) found that recovery time of bermudagrass ( Cynodon dactylon L. Pers.)…”
Section: Introductionmentioning
confidence: 99%
“…Based on a review of the literature, there have been no studies of how cultivation practices such as vertical mowing and solid-tine aerification affect bermudagrass recovery from SDS within the same growing season. Moreover, SDS patches can be slow to recover because of the use of certain preemergence herbicides or metabolites produced by the pathogen that can inhibit shoot regrowth (Beck et al, 2013;Fermanian et al, 1981;Venkatasubbaiah et al, 1994). Therefore, methods to aid in bermudagrass recovery from SDS damage are needed.…”
mentioning
confidence: 99%